Assessing community members’ knowledge and attitude towards Community-Based Education practices in Southern Ethiopia - Demamu Haligamo; Selamawit Honja; Deborah Tagele (Universitas Muhammadiyah Malang, 2022)
The study conducted by the University of Gezira in Sudan indicated that many institutions are not involving the community in the process of Community-Based Education (CBE) program evaluation. Moreover, the community feels that the program is being imposed upon them rather than being available for them. This study aimed to assess community knowledge and attitude towards university health students’ CBE practices and associated factors. The community-based cross-sectional study through systematic random sampling method was conducted on 394 households. Descriptive statistics and logistic regression analysis were conducted by using Statistical Package for Social Science (SPSS) Version.23. Of the 394 individuals interviewed, 188 (47.7%) of them were found to have good knowledge and 229 (58.1%) have good attitude on CBE practices. Concerning the determinant factors, educated respondents, high-income respondents, and student and government employee were likely to have better knowledge of CBE practices than others. In addition, students and government employee also likely to have better attitude towards CBE practices than other occupations. Community members’ knowledge and attitude on certain aspects of the CBE practices were still poor. Thus, the awareness and large participation of community members in the program are needed to increase the popularity of the program.